A Proposed Approach to Informed Consent for Biobanks in China. (5th July 2012) - Liu, Min; Hu, Qingli
ABSTRACT Biobanks are potential goldmines for genomics research. They have become increasingly common as a means to determine the relationship between lifestyle, environmental exposures and predisposition to genetic disease. More and more countries are developing massive national scale biobanks, including Iceland, the UK and Estonia. Now several large‐scale regional and national biobanks are planned in China, such as Shanghai Biobank, which is defined as a key‐element in Shanghai's twelfth five‐year Development Plan of Science and Technology. It is imperative that the authors who are in charge of the ethical aspect of Shanghai Biobank discuss the ethical aspects of these biobanks up front. Currently there is a great deal of heterogeneity in the approaches to informed consent taken by different countries. In the article, after briefly introducing the biobanks in China, we focus on the three most common approaches: classical informed consent, tiered consent, and one‐time general (or blanket) consent, and propose a version of the latter for China, based on compelling arguments.